Report of an evaluation study of Commonwealth Secretariat services in debt management 1993/94-1999/2000 - Belanger, Marcel D. (Commonwealth Secretariat LondonGB, 2000)
Evaluates the Debt Recording and Monitoring System (CS-DRMS) programme aas to its effectiveness, efficiency, relevance, visibility, sustainability and impact. Covers primarily debt managgement projects and activities undertaken during the period 1992/93-1998/99 but also reviews projects from 1985, as appropriate, as well as projects undertaken during the current fiscal year.